1993
DOI: 10.1042/bj2950485
|View full text |Cite
|
Sign up to set email alerts
|

The role of cysteine residues 129 and 329 in Escherichia coli K1 CMP-NeuAc synthase

Abstract: N-Acetylneuraminic acid cytidyltransferase (CMP-NeuAc synthase) of Escherichia coli K1 is sensitive to mercurials and has cysteine residues only at positions 129 and 329. The role of these residues in the catalytic activity and structure of the protein has been investigated by site-directed mutagenesis and chemical modification. The enzyme is inactivated by the thiol-specific reagent dithiodipyridine. Inactivation by this reagent is decreased in the presence of the nucleotide substrate CTP, suggesting that a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…However, exchange of these cysteine residues for other amino acids by site-directed mutagenesis did not change the enzyme activity significantly [590]. In the recombinant enzyme from E. coli two cysteine residues were recognized at the positions 129 and 329, one of which seems to be at or close to the active center, as was shown by inhibition with thiol-specific reagents partly in the presence of CTP.…”
Section: Biosynthesis Of Cmp-sialic Acidsmentioning
confidence: 85%
“…However, exchange of these cysteine residues for other amino acids by site-directed mutagenesis did not change the enzyme activity significantly [590]. In the recombinant enzyme from E. coli two cysteine residues were recognized at the positions 129 and 329, one of which seems to be at or close to the active center, as was shown by inhibition with thiol-specific reagents partly in the presence of CTP.…”
Section: Biosynthesis Of Cmp-sialic Acidsmentioning
confidence: 85%
“…Recombinant, histidine-tagged endo-N-acetylneuraminidase (endo-N), from phage PK1E, was purified from a culture of IPTG (isopropyl-␤-Dthiogalactoside)-induced E. coli BL21(DE3) essentially as described previously (30). CMP-Neu5Ac synthetase was purified as previously described (53,54) from a culture of induced cells expressing pWV200b and had a specific activity of 610.3 units/mg protein, where 1 unit activates 1 mol of Neu5Ac in 1 min at 37°C. Other enzymes were used as induced soluble extracts from cells (BL21 or DH5␣) grown in overexpression broth (Zymo Research, Orange, CA) with 1 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are shown in Table 1. Plasmid pWV200b used for overproduction of E. coli K1 NeuA was derived from pWA1 (53,54) as a template using PCR primers containing EcoRI and HindIII sites. Double-digested PCR product was cloned into similarly digested pKK223-3, placing K1 neuA ϩ under control of the tac promoter and the ribosome binding site of pKK223-3.…”
Section: Methodsmentioning
confidence: 99%
“…Since both the E. coli (42) and rat liver (40) CMP-NeuAc synthetase enzymes are known to be sensitive to NEM, the CHO enzyme was tested. It was found that, whereas very low levels of NEM were slightly stimulatory, the addition of 1 mM NEM to the reaction mixture reduced the CHO activity to about 12%, while the activity of the purified E. coli enzyme was only reduced to 88% under these conditions (Fig.…”
Section: Table I Complementation Analysismentioning
confidence: 99%